Landscapes & Vistas Learn to draw an Assortment of Outdoor Scences Step by Step - Cardaci, Diane (Califarnia Walter Foster, 2012)
capturing details - mastering perspective understanding value - creating dynamic compostions
Arts (Drawing)
1 13
Keywords: Acrylic -- painting -- Technique; Drawing; Landscape painting -- Technique